The reproduction of inequality in the school environment: Considerations on training and educational policies (Research, Society and Development, 2020)
This article aims to present to education professionals aspects related to the importance of Critical Historical Pedagogy in the teaching-learning process through ideas, theories and reflections of scholars and researchers in order to elucidate the evidence of current society marked by the inequalities and injustices that affect the lives of individuals exploited by the ruling class, taking into account the various contradictions found in this sphere. The research is presented in its methodology as a qualitative, bibliographic and documentary research in which the classical literature on educational inequality and the articles found on the theme in the CAPES Journal Portal was reviewed. Among the results found are works that discuss the issue of inequality from Bourdieu's theories in questions on current topics of education. From the information collected we came to the conclusion that despite advances in the last two decades in Brazilian education, with the implementation of progressive educational policies there is still a long way to go so that there is an equal education for all.